A Current Perspective of Systemic Lupus Erythematosus: A Literature Review - Wibowo, Cakraningrum Jakti Giza; Rahmadinie, Amalia (Journal of Diverse Medical Research: Medicosphere, 2024)
Background. Systemic lupus erythematosus (SLE), is a chronic autoimmune disease that affects various organ systems in the body. This disease is characterized by an abnormal immune reaction, in which the body's immune system attacks the body's own tissues, resulting in inflammation and damage. Symptoms of lupus vary greatly, ranging from fatigue, joint pain, skin rashes, to serious complications such as kidney and heart damage. Systemic lupus erythematosus (SLE) is characterized by dysfunction of the immune system and is clinically heterogeneous, presenting with renal, dermatological, neuropsychiatric, and cardiovascular. Methods. The research method used was literature review using electronic databases through national and international journals such as Google scholar and ScienceDirect as well as health articles such as Cleveland Clinic. The inclusion criteria used by the authors were to limit articles or journals published in the last five years starting from 2019 to 2024. Disscusion. Systemic lupus erythematosus (SLE) classification criteria are often chosen based on tradition, consensus and statistics, without considering deeper etiological and pathogenetic aspects. This process can result in a lack of scientific objectivity, as it does not explore causal relationships between criteria and disease mechanisms. Conclusion. Systemic Lupus Erythematosus (SLE) is a systemic autoimmune disease characterized by aberrant immune system reactions, affecting various organs in the body. Genetic, environmental and hormonal factors contribute significantly to the development of this disease, which is more common in women of reproductive age.   Keywords: Systemic Lupus Erythematosus (SLE), Autoimmune, Symptoms, Diagnosis